Pendampingan Siswa melalui Program Tahfizh One Day One Line di SDN 02 V Koto Kampung Dalam Kabupaten Padang Pariaman - Eldarifai Eldarifai; Martin Kustati; Rezki Amelia; Nurhasnah Nurhasnah (Jurnal Kabar Masyarakat, 2024)
This mentoring activity aims to increase students participation for the optimal achievement of the tahfiz programme "One day one line", so that later before graduating from elementary school student’s memorise at least 1 juzz Al-Quran. The rise of the Tahfizh programme in Islamic Education Institutions is a challenge that must be faced by general education institutions. The presence of the Tahfizh programme is a breakthrough that must be optimised for its implementation as a positive culture in schools. The term positive culture itself is a concept that comes along with the emergence of the concept of Merdeka Belajar. Therefore, assistance to all teachers is a necessity and inseparable in supporting the running of the programme. Moreover, elementary school teachers whose backgrounds are general education, so they need assistance to guide students in optimising the implementation of the Tahfizh Quran One Day One Line program.  The method of this assistance is the Tajweed and Nagham Integration Method in improving Quran memorisation.With the results of mentoring is that the average achievement is about 48% of students who complete the memorisation target per semester.